Visualization of microbial biofilms in case of digestive disorders in lambs - E. M. Lenchenko; N. P. Sachivkina; D. A. Blumenkrants; A. Yu. Arsenyuk (Ветеринария сегодня)
The paper demonstrates morphometric and densitometric parameters of microbial biofilms recovered from lambs with digestive disorders. Changes of quantitative and species composition of the intestinal microbiocenoses in the lambs with digestive disorders were compared with the ones of the clinically healthy lambs. Light microscopy results demonstrated formation of three-dimensional biofilm structure in the form of dense grid consisting of gram-negative and gram-positive bacteria, yeast cells, hyphas and pseudohyphas surrounded with intracellular polymer matrix. Presence of blastospores aided to the increased number of cells attached to the substrate, and biofilm was formed, which consisted of rod and round cells attached to the microfungi cells. In the process of dispersion that occurred during the destruction of the intercellular matrix and bacterial and yeast cell detachment, branched structures separated from the microcolonies and colonized microorganism- free regions of the substrate. The intensity of biofilm formation by the microorganisms under study was evaluated by optic density measurement in 48 hours of cultivation. Fluorescence microscopy results demonstrated that the dynamics of changes of the viable microbial structures was specified by intermittent periods of increased or decreased biofilm formation intensity. Cells characterized by active growth and replication and forming alternating subpopulations were detected in the examined microbial cultures. When determining the viability of the microorganisms in the biofilms, the viable (green fluorescence) and non-viable (red fluorescence) cells were differentiated.